5/7. -5/7+ 5/7.-2/11-5/7.-14/11
5/7×5/11+5/7×2/11-5/7×14/11
\(\dfrac{5}{7}\left(\dfrac{5}{11}+\dfrac{2}{11}-\dfrac{14}{11}\right)=\dfrac{5}{7}\times-\dfrac{7}{11}=\dfrac{-5}{11}\)
= 5/7 x ( 5/11 + 2/11 - 14/11 )
= 5/7 x -7/11
= -5/11
5/7 x ( 5/11 + 2/11 - 14/11) = 5/7 x -7/11 = -5/11
5/7×5/11+5/7×2/11-5/7×14/11
5/7×5/11+5/7×2/11-5/7×14/11
= 5/7 x ( 5/11 + 2/11 - 14/11 )
= 5/7 x -7/11
= -35/77
thu gọn các biểu thức sau
a)C=3^14+3^15+3^16+3^17+...+3^n
b)D=3^11+3^14+3^17+3^20+...+3^2021
c) E= -5^2-5^4-5^6-5^8-...-5^1000
d)F=-5^21-5^23-5^25-5^27-...-5^2019
e)M=7^2-7^4+7^6-7^8+...-7^1000
d)N=-12+11^2+11^3-11^4-11^5+...+11^498+11^499
b: \(27D=3^{14}+3^{17}+...+3^{2024}\)
\(\Leftrightarrow26D=3^{2024}-3^{11}\)
hay \(D=\dfrac{3^{2024}-3^{11}}{26}\)
c: \(25E=-5^4-5^6-...-5^{1002}\)
\(\Leftrightarrow24E=-5^{1002}+5^2\)
hay \(E=\dfrac{-5^{1002}+5^2}{24}\)
5/7*12/11+9/7*2/11-5/7*14/11
\(\frac{5}{7}.\frac{12}{11}+\frac{9}{7}.\frac{2}{11}-\frac{5}{7}.\frac{14}{11}\)
\(=\frac{1}{7}.\frac{1}{11}.\left(5.12+9.2-5.14\right)\)
\(=\frac{1}{77}.\left(60+18-70\right)\)
\(=\frac{1}{77}.8=\frac{8}{77}\)
Thực hiện phép tính có thể
5/7×5/11+5/7×2/11-5/7×14/11
\(\dfrac{5}{7}\)x\(\dfrac{5 }{11}\)\(+\dfrac{5}{7}\)\(\text{x}\dfrac{2}{11}\)\(-\dfrac{5}{7}\)\(\text{x}\dfrac{14}{11}\)
`5/7xx5/11+5/7xx2/11-5/7xx14/11`
`=5/7xx(5/11+2/11-14/11)`
`=5/7xx(-7/11)`
`=-5/11`
\(\dfrac{5}{7}\times\dfrac{5}{11}+\dfrac{5}{7}\times\dfrac{2}{11}-\dfrac{5}{7}\times\dfrac{14}{11}\)
=\(\dfrac{5}{7}\times\left(\dfrac{5}{11}+\dfrac{2}{11}-\dfrac{14}{11}\right)\)
=\(\dfrac{5}{7}\)\(\times-\dfrac{7}{11}\)
=\(-\dfrac{5}{11}\)
Chúc bạn học tốt nhé
57×(511+211−1411)57×(511+211−1411)
=×−711×−711
=
5/7 . 9/11 + -5/7 . -2/11 + 1/14
\(\dfrac{5}{7}\cdot\dfrac{9}{11}+\dfrac{-5}{7}\cdot\dfrac{-2}{11}+\dfrac{1}{14}=\dfrac{45}{77}+\dfrac{10}{77}+\dfrac{1}{14}=\dfrac{5}{7}+\dfrac{1}{14}=\dfrac{10}{14}+\dfrac{1}{14}=\dfrac{11}{14}\)
\(\dfrac{5}{7}.\dfrac{9}{11}-\dfrac{5}{7}.-\dfrac{2}{11}+\dfrac{1}{14}=\dfrac{5}{7}.\left(\dfrac{9}{11}+\dfrac{2}{11}\right)+\dfrac{1}{14}=\dfrac{5}{7}.1+\dfrac{1}{14}=\dfrac{10+1}{14}=\dfrac{11}{14}\)
5/7 x 6/11 + 5/11 x 1/7 - 5/7 x 14/11
\(\dfrac{5}{7}\cdot\dfrac{6}{11}+\dfrac{5}{11}\cdot\dfrac{1}{7}-\dfrac{5}{7}\cdot\dfrac{14}{11}\)
\(=\dfrac{5}{7}\cdot\dfrac{6}{11}+\dfrac{5}{7}\cdot\dfrac{1}{11}-\dfrac{5}{7}\cdot\dfrac{14}{11}\)
\(=\dfrac{5}{7}\cdot\left(\dfrac{6}{11}+\dfrac{1}{11}-\dfrac{14}{11}\right)\)
\(=\dfrac{5}{7}\cdot\dfrac{-7}{11}=\dfrac{-5}{11}\)
Bài 1 . Tính nhanh :
A = 6/7 + 1/7 . 2/7 + 1/7 . 5/7
B = 4/9 . 13/3 - 4/3 . 40/9
M = 8/3 . 2/5 . 3/8 . 10 . 19/2
N = 5/7 . 5/11 + 5/7 . 2/11 - 5/7 . 14/11
B=4*13/9*3-4/3*40/9
B=4/3*13/9-4/3*40/9
B=4/3*(13/9-40/9)
B=4/3*(-27)/9
B=4*(-3)/9
B=-4
A=6/7 + 1/7.(2/7+5/7)
A=6/7 + 1/7.7/7=6/7+1/7.1
A=6/7+1/7=7/7=1
M=8/3*2/5*3/8*10*19/2
M=(8/3*3/8)*(2/5*10)*19/2
M=1*4*19/2
M=28